Circular RNA hsa_circ_0072309 inhibits non-small cell lung cancer progression by sponging miR-580-3p. Issue 5 (4th May 2020) - Pang, Wenguang; Huang, Fengliu; Zhang, Xin; Ye, Min; Huang, Yanming; Huang, Xiufang; Pang, Jingzhuo; Cai, Chengjie; Wang, Zheng
Abstract: Objective: Non-small cell lung cancer (NSCLC) continues to top the list of cancer mortalities worldwide. Early diagnosis and therapeutic interventions targeting NSCLC is becoming the world's significant challenge. Circular RNAs (circRNAs) are emerging as a group of potential cancer biomarkers. Materials and methods: Quantitative real-time PCR (qRT-PCR) was employed to examine the expression of circ_0072309 in NSCLC tissues and cell lines. Cell counting kit 8 (CCK-8), wound healing and Transwell assays were used to analyze cell proliferation, migration and invasion in A549 and H1299 cells. The relationship between circ_0072309 and miR-580-3 was analyzed by Luciferase reporter and RNA pull down assays. Results: We screened circ_0072309 from Gene Expression Omnibus and found that circ_0072309 was lowly expressed in NSCLC tissues and cell lines. The transfection of circ_0072309-overexpressing vector significantly suppressed the cell proliferation, migration and invasion in A549 and H1299 cells. We predicted that miR-580-3p is a target of circ_0072309 by using publicly available bioinformatic algorithms Circinteractome tool and confirmed that circ_0072309 directly bound to miR-580-3p. Furthermore, the addition of miR-580-3p mitigated the blockage of cell proliferation, migration and invasion induced by circ_0072309. Conclusions: These data showed that circ_0072309 inhibits the progression of NSCLC progression via blocking the expression of miR-580-3p. These findings revealed the anti-tumor role of circ_0072309 during the development of NSCLC and provided a novel diagnostic biomarker and potential therapy for NSCLC.